The involvement of an insurance company in property investment. Case study: Malaysia National Insurance Sdn. Bhd. / Siti Rosmiza Abd Rahman - Abd Rahman, Siti Rosmiza (1994)
Malaysia is rapidly growing into a highly develop country which is well known throughout the world. With its political and economic stability, various types of industries ranging from a highly sophisticated technological industry to the production of foods. Insurance business is relatively new, however, within the short space of time this industry has made a notable contribution to the economic development of the country. As a result of its efficient services to both the government and the private sectors, the insurance industry has develop into a major domestic industry in Malaysia. The insurance industry continued to move forward to explore the many opportunities created by an expanding economy with increasingly diversified and sophisticated insurance needs.